ChemInform Abstract: N, N′‐Dioxide‐Magnesium Ditriflate Complex‐Catalyzed Asymmetric α‐Hydroxylation of β‐Keto Esters and β‐Keto Amides. Issue 51 (17th December 2013) - Yin, Chengkai; Cao, Weidi; Lin, Lili; Liu, Xiaohua; Feng, Xiaoming
Abstract Chiral N, N‐dioxide magnesium complexes are described as efficient catalysts for the α‐hydroxylation of cyclic 1‐tetralone derived β‐keto esters.